Piezoelectric energy harvesting with single and multiple condensed cavities. (25th January 2017) - Srinivasulu Raju, S.; Umapathy, M.; Uma, G.
ABSTRACT: The piezoelectric energy harvester using cantilever beam is most popular for converting ambient vibration into electrical energy and generates maximum voltage when the beam vibrates at its resonant frequency. In this direction, the structural modification of the energy harvesters provides greater improvement in the performance of the harvester. This work shows the analytical modeling and experimentation of a piezoelectric energy harvester with multiple condensed cavities. The performance of the piezoelectric energy harvesters is enhanced by introducing the condensed cavities (length of the cavities is exactly at half of the length of the piezoelectric element) in beam. The proposed structures are modeled analytically using Euler-Bernoulli beam theory and fabricated for experimental investigations. The analytical and experimental results demonstrate that the output voltage of the energy harvester can be increased with two condensed cavities as compared to the harvester with single, three and four condensed cavities. The output voltage of the harvester with two, three and four condensed cavities is 34.2%, 27.70% and 14.43% higher as compared with the single condensed cavity in beam.